ELEMENTARY GAMES IN BASKETBALL TRAINING - Edin Užičanin, (Sport Scientific And Practical Aspects, 2025)
The games in sport training are applied as other training operators, in reference to other goals in separate part of sport training. In that way for example, one strength training with usual contents can be replaced with training which contain elementary games that with its content influnce at same ability that we want to achieve. In this work are shown games used for development of speed, strength, flexibility, endurance and other basic abilities, but which in specific measure create positive mood and have equal influence as other kinetic operators.